'There's no future here': The time and place of children's migration aspirations in Peru. (June 2015) - Crivello, Gina
Highlights: I explore the social contexts in which migration aspirations are generated in Peru. Analysis relies on a biographical approach to migration drawing on multi-generational accounts. Children's aspirations are not just about the future. Aspirations influence actions and reflect current orientations and realities. Aspirations are emplaced, constituted in and through particular spaces. Abstract: This article examines young Peruvians' aspirations and the role of migration in their imagined futures, from a generational perspective. The data come from Young Lives, a long-term study of childhood poverty combining survey and qualitative approaches with children and their parents. The paper uses a biographical approach that sees migration as part of individual biographies as well as social structures and life course processes. The aim is to deepen understanding of the social contexts in which aspirations for and by children are generated, paying close attention to family migration histories, dynamic household contexts, and children's migration networks. The analysis focuses on the time-spaces of migration aspirations, showing the way past, present and future are interconnected. It also emplaces aspirations by focusing on the way aspirations by and for children are constituted in and through particular places. The conclusion reflects on the role of poverty and argues that 'aspirations' are about much more than abstract 'futures'; they orient actions in the present and say a great deal about young people's current realities and relationships.